SPEECH ACTS OF TEACHER AND STUDENTS IN INDONESIAN LANGUAGE LEARNING IN GRADE XI-3 SMA NEGERI 5 MANDAU - Fara windy ayoe azzahra; Rika Ningsih (SOSIOEDUKASI, 2026)
Learning in the classroom is inseparable from the communication process between teachers and students. Every explanation, question, or response conveyed in the learning process is a form of speech that has a specific purpose. However, in learning activities, there is often not much study of how the forms of speech that appear during interactions. Therefore, this study aims to describe and analyze the forms of illocution speech used by teachers and students in learning Indonesian in grades XI-3 of SMA Negeri 5 Mandau. This study uses a qualitative approach with a descriptive type of research. The method used is content analysis to examine speech that appears during the learning process. The research data is in the form of teacher and student speech which is included in the act of illocution. The data source in this study is the interaction of Indonesian language learning in grades XI-3 of SMA Negeri 5 Mandau on news text materials and scientific papers. Data collection techniques were carried out through observation, documentation, recording, listening methods, and recording methods during four learning meetings. The results of the study showed that 91 acts of illocution were found consisting of 37 acts of assertive speech, 31 acts of directive speech, 14 acts of commissive speech, and 9 acts of expressive speech, while declarative acts of speech were not found. Assertive and directive speech acts appear the most because teachers often provide explanations, information, and directions to students during learning. Meanwhile, commissive and expressive speech acts appear in smaller amounts, usually related to promises, responses, or expressions of feelings in the learning process. Based on the results of the study, it can be concluded that the interaction between teachers and students in learning Indonesian in grades XI-3 of SMA Negeri 5 Mandau is more of an act of illocution speech that is explanatory (assertive) and directs (directive) learning activities. This shows that communication in learning is quite active and helps support the learning process in the classroom.